Evaluation of thyroid nodules by Gray scale and Doppler sonography and correlation with fine needle aspiration cytology - Singh, Dalpat; Makwana, Mohan; Verma, G. L.; Lal, Kanwar (International Surgery Journal, 2017)
Background: Nodular goiter is a worldwide disease and is encountered commonly in clinical practice by primary care physicians, endocrinologist, surgeons and otolaryngologists. The solitary thyroid nodule is common presentation & the incidence of carcinoma in single thyroid nodule is between 8-20% and in multinodular goiter is about 5%. Ultrasonography (USG), both Gray scale and color Doppler is useful in diagnosis of various thyroid lesions and can be utilized to correlate USG features with histopathological findings wherever possible. Methods: The present study was conducted in the Department of Radio Diagnosis and Modern Imaging, Govt. Medical College, Kota, Rajasthan, India. Participants after understanding the study protocol and procedure, were asked to give their written consent for the study. Cross sectional study was conducted with 50 patients of all age group presenting with thyroid nodule. 50 patients of all age group attending outdoor and indoor of E.N.T. and other surgical department of this hospital presenting with thyroid nodule. Results: Out of 50 cases, majority of patients were between 21-40 years of age, most of the malignant cases were in 41-50 years of age group. Majority had involvement of right lobe of thyroid (44%), 74% had single thyroid nodule. Lesions having multiple nodules were mostly benign in nature. Malignant lesions were mostly seen in single thyroid nodule. Higher resistive index (RI) value (in 83.3% cases) and lower peak systolic velocity (PSV) (in 100% cases) were found in malignant lesion as compared to benign lesion. Thus, pulse Doppler study has found to be very useful in deciding the nature of the lesion. Most common malignancies are anaplastic carcinoma and Squamous cell carcinoma. All cases diagnosed malignant on USG were proved to be malignant on fine needle aspiration cytology (FNAC) and vice versa. Conclusions: An excellent correlation was seen in diagnosis of thyroid lesions between sonography (Gray scale, color Doppler flow Imaging (CDFI) and power Doppler (PD)) and histopathology. Sonography (Gray scale and Doppler together) was 98% sensitive in diagnosis of thyroid lesions.